Role of Women In MGNREGA In Kaithal District of Haryana India - Mukesh Chahal; Dr. Pardeep Kumar; Dr. Kiran Lamba (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2021)
Poverty and unemployment remain the main issue in India. These issues are mostly found in rural areas. The Government of India has been formulating various programs for rural growth and poverty eradication. One such programmed is the Mahatma Gandhi National Rural Employment Guarantee Act (MGNREGA), a successful program in promoting gender equality, empowering women, and creating long-lasting infrastructure in rural areas providing employment. The study was conducted in the Kaithal district of Haryana covering a sample of 100 beneficiaries. The collected data has been analyzed using simple frequency and percentage analysis, descriptive analysis, and correlation analysis. The results have revealed that the program was successful in empowering the women of the district.